2017
DOI: 10.5812/cardiovascmed.34767
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in the predictive role of high depressive symptoms on incident heart disease over 18 years: Results from the health and retirement study

Abstract: Background: Studies have investigated racial differences in the relationship between depression and CVD mortality. Objectives: This study tested the hypothesis that race moderates the effect of baseline depressive symptoms on subsequent heart disease among a nationally representative sample of Black and White older Americans. Patients and Methods: Data came from ten waves of the health and retirement study (HRS), a nationally representative longitudinal study of US adults over age 50. The present study followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
11
1
Order By: Relevance
“…In agreement with the differential effect (susceptibility) theory [1,2,3,8], a number of recent studies have found evidence suggesting differential effect of depression on mastery and self-esteem (dysfunctional attitudes about self) across race and ethnic groups [10,12,13,21]. Racial and ethnic group differences have also been found in the effects of depression on hopelessness (dysfunctional attitudes about future) [22].…”
Section: Introductionmentioning
confidence: 76%
“…In agreement with the differential effect (susceptibility) theory [1,2,3,8], a number of recent studies have found evidence suggesting differential effect of depression on mastery and self-esteem (dysfunctional attitudes about self) across race and ethnic groups [10,12,13,21]. Racial and ethnic group differences have also been found in the effects of depression on hopelessness (dysfunctional attitudes about future) [22].…”
Section: Introductionmentioning
confidence: 76%
“…Although we adjusted for multiple confounders, residual confounding due to other chronic medical conditions, such as asthma, chronic obstructive pulmonary disease, cancer, or arthritis, which may be comorbid to depression 56 and which could lead to arterial stiffening, cannot be ruled out. Finally, the association between CVD markers and depression may differ according to race; [57][58][59][60] however, our study population consisted mainly of white people, therefore we could not investigate such effects.…”
Section: Limitationsmentioning
confidence: 99%
“…Built on the differential effect hypothesis (Assari, 2016b,d; Assari and Lankarani, 2016b; Assari and Sonnega, 2016), we conducted the current study to compare Black and White American older adults for the reciprocal longitudinal associations between depressive symptoms and mastery over time. This hypothesis is in line with what Belsky and others have called ‘differential susceptibility to environmental influences’ or ‘differential susceptibility to the context’ (Belsky, 1997; Boyce and Ellis, 2005; Belsky et al, 2007; Belsky and Pluess, 2009).…”
Section: Introductionmentioning
confidence: 99%